“TEACHING IS AN ART” METODE TERAMPIL DAN SUKSES MENDIDIK DALAM PERSPEKTIF HADIS - Uswatun Hasanah (STIT Al-Marhalah Al-Ulya Bekasi, 2022)
AbstrackSkilled and successful in educating is not only caused by a lot of knowledge and knowledge. Because educating is a work of art related to learning activities. Especially during the pandemic, when students and teachers cannot meet each other face to face. The art of teaching or the art of education is a factor that determines the success of learning. Among the educators who are successful and influential at the international level is Muhammad Rasulullah. The lessons he conveyed were not only limited to the friends who lived with him, but all Muslims until the end of time were obedient and carried out what the Prophet had taught even though the Educator had long died. This paper aims to examine in more depth the methods used by the Prophet so that they can be skilled and successful in educating. The method used in this research is thematic hadith. Inventory of authentic hadiths that talk about educational methods, select hadiths that focus on the main idea of research, then examine the meaning of hadith and analyze. The Hadith of Muslim history number 4830 describes a method that has succeeded in bringing success to the teaching of the Prophet, namely using the exemplary method. Although not face to face (online) As a religion, Islam wants its people to be role models in all aspects. Because exemplary is a learning method that has a great influence both on education that aims to increase knowledge, proficient in certain skills and form a commendable attitude and personality. Keywords: Teaching is an Art, Skilled Method, Successful Education, Hadith Perspective